Pengaruh Harga, Promosi, dan Kualitas Produk terhadap Keputusan Pembelian Konsumen pada Platform E-Commerce - Beni Chandra Purba (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The rapid advancement of digital technology and the increasingly widespread penetration of the internet have significantly driven the growth of e-commerce in Indonesia, leading to notable changes in consumer behavior in making purchasing decisions. This condition requires business actors to comprehensively understand marketing factors that play a crucial role in influencing consumer decisions on e-commerce platforms, particularly those related to price, promotion, and product quality. The research problem of this study focuses on how these three variables shape consumer purchasing decisions amid increasingly intense e-commerce competition. This study aims to analyze the influence of price, promotion, and product quality on purchasing decisions in e-commerce by employing a qualitative approach through a literature review of various relevant scholarly sources, including both national and international journals. The findings indicate that competitive pricing aligned with consumers’ perceived value has a strong influence on attracting purchase intentions, while appropriate, sustainable, and communicative promotional strategies are able to enhance consumer awareness and purchase motivation. On the other hand, product quality is proven to be a key determinant in building trust, satisfaction, and consumer loyalty in online transactions. The conclusion of this study confirms that price, promotion, and product quality simultaneously contribute positively and significantly to e-commerce purchasing decisions. The novelty of this scholarly work lies in its conceptual synthesis that integrates these three variables within the context of Indonesian e-commerce consumer behavior, providing a holistic understanding that can serve as a strategic basis for decision-making among digital business practitioners in the technology-based economic era.